The influence of accounting internal control and human resources capacity on reliability and timeliness of regional government financial reporting (a study in Special Region of Yogyakarta Province) - Dianila Oktyawati; Faridiah Aghadiati Fajri (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
Regional autonomy allows regions to hold the authority to manage their own regions. It also raises the responsibility that must be fulfilled by the regional government, namely financial reporting as a means of accountability. Reliability and timeliness are two important elements in financial information for the right decision making. There are several factors that can influence reliability and timeliness. This study aims to examine the effect of accounting internal controls and human resources capacity on the reliability and timeliness of financial reporting in local governments. The object of this research was the head and staff of the Regional Financial and Asset Agency (BKAD) in the Special Region of Yogyakarta province. Data collection was done through questionnaires, which were then analyzed using multiple linear regression analysis. The results of this study indicate that accounting internal control and human resources capacity have a significant influence on the reliability and timeliness of financial reporting in the local governments in the Special Region of Yogyakarta Province.